(untitled) (Semiárida, 2020)
This work was realized at the Ea. Los Guadales (Depto. Caleu-Caleu, La Pampa) with the objetive of determine the available phytomass. vegetable cover, density of grasses, crown weight and roots weight at a depth of 0-20 and 20-40 cm in an area dominated by Pappophorum caespitosum and isolated shrubs. The vegetable cover was of 70 %, the litter of 27% and the bare soil of 3%. The monthly density of the grasses vas of 17 % pl/m2. The aerial phytomass had an average value of 374.8 gMS/m2, the litter of 623,2 gMS/m2 and the crowns of 152 gMS/m2. The average weights of the roots were of 1427,6 gMS/m2 in the first 20 cm of depth (68.1% of all the evaluated roots) and of 67,1 gMS/m2 in the next 20 cm.